Dietary fat composition influences glomerular and proximal convoluted tubule cell structure and autophagic processes in kidneys from calorie‐restricted mice. Issue 3 (8th February 2016) - Calvo‐Rubio, Miguel; Burón, Mª Isabel; López‐Lluch, Guillermo; Navas, Plácido; de Cabo, Rafael; Ramsey, Jon J.; Villalba, José M.; González‐Reyes, José A.
Summary: Calorie restriction (CR) has been repeatedly shown to prevent cancer, diabetes, hypertension, and other age‐related diseases in a wide range of animals, including non‐human primates and humans. In rodents, CR also increases lifespan and is a powerful tool for studying the aging process. Recently, it has been reported in mice that dietary fat plays an important role in determining lifespan extension with 40% CR. In these conditions, animals fed lard as dietary fat showed an increased longevity compared with mice fed soybean or fish oils. In this paper, we study the effect of these dietary fats on structural and physiological parameters of kidney from mice maintained on 40% CR for 6 and 18 months. Analyses were performed using quantitative electron microcopy techniques and protein expression in Western blots. CR mitigated most of the analyzed age‐related parameters in kidney, such as glomerular basement membrane thickness, mitochondrial mass in convoluted proximal tubules and autophagic markers in renal homogenates. The lard group showed improved preservation of several renal structures with aging when compared to the other CR diet groups. These results indicate that dietary fat modulates renal structure and function in CR mice and plays an essential role in the determination of health span in rodents.